2009
DOI: 10.1593/neo.09878
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-Targeting Cytotoxin and Endoplasmic Reticulum Stress-Inducing Drug Synergize to Kill Cancer Cells

Abstract: Diverse physiological and therapeutic insults that increase the amount of unfolded or misfolded proteins in the endoplasmic reticulum (ER) induce the unfolded protein response, an evolutionarily conserved protective mechanism that manages ER stress. Glucose-regulated protein 78/immunoglobulin heavy-chain binding protein (GRP78/BiP) is an ER-resident protein that plays a central role in the ER stress response and is the only known substrate of the proteolytic A subunit (SubA) of a novel bacterial AB(5) toxin. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 33 publications
1
59
0
Order By: Relevance
“…Therapeutics targeting GRP78 have recently emerged and have shown anti-tumor activity in solid tumors. 16,[51][52][53][54] Whether these and other agents capable of suppressing GRP78 expression or activity can be applied for suppression of leukemogenesis warrants vigorous investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics targeting GRP78 have recently emerged and have shown anti-tumor activity in solid tumors. 16,[51][52][53][54] Whether these and other agents capable of suppressing GRP78 expression or activity can be applied for suppression of leukemogenesis warrants vigorous investigation.…”
Section: Discussionmentioning
confidence: 99%
“…We found that EGF-SubA rapidly accumulates in cancer cells via EGFR-mediated endocytosis and is cytotoxic to both growing and confluent EGFR-expressing cells in the picomolar concentration range, and that this toxicity is mediated by cleavage of GRP78 (Backer et al, 2009). In this respect, despite different routes of intracellular delivery, EGF-SubA is similar to the bacterial SubAB holotoxin (Paton et al, 2006).…”
Section: Targeting the Upr In Cancer Cells Via Selective Cleavage Of mentioning
confidence: 86%
“…Viability of control untreated cells was defined as 100%. For these cell lines, the IC 50 values differ 20-fold, 2 pM for PC3 cells and 40 pM for MDA231luc cells, despite similar levels of EGFR and GRP78 in these cells (Backer et al, 2009). …”
Section: Analysis Of Selective Grp78 Cleavage In Cancer Cellsmentioning
confidence: 87%
See 2 more Smart Citations